KEPEMIMPINAN KHULAFAUR RASYIDIN DALAM PERADABAN ISLAM - Al Ayyubi, Ibnu Imam; Fauziah, Zairina; Arifah, Hasanah; Hartati, Ratna Dewi; Herdiansyah, Risman (Jazirah: Jurnal Peradaban dan Kebudayaan, 2024)
This research aims to complement existing research regarding the leadership of Khulafaur Rasyidin in Islamic civilization which is described comprehensively and explained partially. This research is descriptive qualitative research with a literature study approach that refers to several sources of research data and data collection techniques in the form of a study of Islamic civilization during the time of Khulafaur Rasyidin. Data collection was carried out by searching and reconstructing from various sources such as articles in journals, books, and previous research that were relevant to the research study, which were then analyzed in a primordial manner. The focus of the research that will be addressed is Khulafaur Rasyidin's leadership in Islamic civilization. The data collection technique used in this research is the library research method, namely library research with the data analysis technique used in this research is the hermeneutic method. In this research, it can be concluded that during the time of the Rasyidin khulafaur, namely Abu Bakar Ash-Shiddiq, Umar Bin Khattab, and Ali bin Abi Talib, they had differentiated characteristics regarding their leadership during the Islamic civilization period where Abu Bakar implemented a model of government that had the characteristics of a monarchy, similar to a kingdom system, with himself as Caliph or head of government. Umar had an administrative system which was mostly an economic system and judicial organization. Then Usman was the first to form a navy which succeeded in expanding Islamic power to various regions. Meanwhile, Caliph Ali took a political policy that was said to be quite risky, because this policy caused hatred from high-ranking officials during Usman's caliphate.